From Education to Research - Paulo Pinho (U.Porto Journal of Engineering, 2023)
This paper provides a brief account of the creation and evolution of the CITTA R&D Unit, which, in the early 2000s, emerged from the SPTA, the Planning Division of FEUP’s Civil Engineering Department (DEC). Attention is given to the birth of the Centre, marked by the convergence of some favourable external and internal conditions, which also shaped its composition, structure, and scientific scope. The CITTA development phase is then characterised. This phase was influenced by the pluriannual evaluation of the FCT in 2008 and, a few years later, by the integration of a large group of researchers from the University of Coimbra, which justified the profound revision of the CITTA’s internal regulations. Finally, the paper addresses the Centre's consolidation phase, emphasising the role and importance of the two last pluriannual FCT evaluations, the relative position of the Centre's publication performance compared to similar centres in Europe, and its strategic plan, conceived around the low-carbon cities paradigm.Author Keywords. civil engineering, Porto Faculty of Engineering, Planning Division.